2002
DOI: 10.4049/jimmunol.169.11.6498
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Leukocyte Lipid Body Formation In Vivo: Innate Immunity Elicited Intracellular Loci Involved in Eicosanoid Metabolism

Abstract: Lipid bodies are rapidly inducible, specialized cytoplasmic domains for eicosanoid-forming enzyme localization, which we hypothesize to have specific roles in enhanced inflammatory mediator production during pathological conditions, including sepsis. However, little is known about the origins, composition, or functions of lipid bodies in vivo. We show that lipid body numbers were increased in leukocytes from septic patients in comparison with healthy subjects. Analogously, the intrathoracic administration of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
1
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(194 citation statements)
references
References 65 publications
9
172
1
10
Order By: Relevance
“…Recent work has indicated that LBs in a variety of cell types are not merely lipid reservoirs (2,3). In phagocytes engaged in inflammation, LBs have been mainly implicated in the synthesis of eicosanoids (4,5). The AA-releasing enzyme cPLA 2 , its activating mitogenactivated protein kinases, and the eicosanoid-generating enzymes 5-lipoxygenase and cyclooxygenase all have been found on the surface of LBs in several leukocyte types.…”
Section: Distribution Of Lbs Around Phagosomes In Wt and Gp91 Phox -Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has indicated that LBs in a variety of cell types are not merely lipid reservoirs (2,3). In phagocytes engaged in inflammation, LBs have been mainly implicated in the synthesis of eicosanoids (4,5). The AA-releasing enzyme cPLA 2 , its activating mitogenactivated protein kinases, and the eicosanoid-generating enzymes 5-lipoxygenase and cyclooxygenase all have been found on the surface of LBs in several leukocyte types.…”
Section: Distribution Of Lbs Around Phagosomes In Wt and Gp91 Phox -Dmentioning
confidence: 99%
“…In leukocytes engaged in inflammation, an increased number of LBs is usually found (4,5). Rapid LB induction by priming agents such as cis-unsaturated fatty acids, protein kinase C activators, or platelet-activating factor has been correlated with an enhanced capacity to generate eicosanoids (6,7), which are powerful mediators of inflammation (8).…”
mentioning
confidence: 99%
“…40,82 Macrophage lipid bodies, which are formed by different stimuli and pathological conditions including obesity-induced inflammation, ox-LDL-and LPS-induced inflammation or bacterial infection, are increasingly recognized as organelles with key roles in inflammation. [83][84][85][86][87][88] Under inflammatory conditions, they compartmentalize MAP kinases, cPLA 2 , eicosanoid-forming enzymes and are involved in the enhanced eicosanoid synthesis. [84][85][86][87][88][89] In addition, human colon adenocarcinoma cell lines and colon cancer biopsies from patients have recently been shown to exhibit a drastic increase in ADRP and COX-2-enriched lipid bodies.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…[83][84][85][86][87][88] Under inflammatory conditions, they compartmentalize MAP kinases, cPLA 2 , eicosanoid-forming enzymes and are involved in the enhanced eicosanoid synthesis. [84][85][86][87][88][89] In addition, human colon adenocarcinoma cell lines and colon cancer biopsies from patients have recently been shown to exhibit a drastic increase in ADRP and COX-2-enriched lipid bodies. 90 Furthermore, inhibition of lipid body formation leads to inhibited PGE 2 production and correlates with diminished cancer cell proliferation.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…Diferente dos adipócitos, nos leucócitos a formação de CLs é específica e dependente do estímulo [76][77][78] , do tipo celular [79] e de receptores [77,[80][81][82] . Os CLs são tipicamente escassos em leucócitos não ativados, mas caracteristicamente aumentados em número e tamanho in vitro e in vivo em células inflamatórias [76,[82][83][84][85][86] .…”
Section: Corpúsculos Lipídicos E Sua Inibição Farmacológicaunclassified